The potential of accelerator-based techniques as an analytical tool for forensics: The case of coffee. (June 2022) - Chytry, P.; Souza, G.M.S.; Debastiani, R.; dos Santos, C.E.I.; Antoine, J.M.R.; Banas, A.; Banas, K.; Calcagnile, L.; Chiari, M.; Hajdas, I.; Molnar, M.; Pelicon, P.; et al.
Abstract: We discuss how different accelerator-based techniques can be employed synergistically as a powerful analytical tool for forensic studies of foodstuff. Brazilian and Jamaican coffees were chosen as a showcase due to its popularity and potential risk of adulteration and/or falsification. Comprehensive characterization of major and trace elements, age since production and compound contents were achieved using different techniques, including PIXE (Particle-Induced X-ray Emission), FTIR (Fourier Transform Infrared), and AMS- 14 C (Accelerator Mass Spectrometry – Radiocarbon Analysis). While PIXE provides information on the elements present in the samples, FTIR probes the types of compounds through their vibrational spectra. Finally, AMS- 14 C is capable of dating organic samples regarding their harvesting time. Five different laboratories from research institutions around the world took part in the experiments. The integration of the results obtained with different techniques provided multifaceted perspectives on the coffee under study, thus allowing a direct assessment of the material for forensic purposes such as authentication, determination of provenance, and combat counterfeiting. Highlights: Accelerator-based techniques helping forensic studies of coffee. PIXE: provides information on the elemental profile of coffee. AMS-14C: provides information on the date of production. ATR-FTIR: provides information on the molecular profile of coffee. Overall results show a synergetic integration of these techniques.